Unique Members of the Adipokinetic Hormone Family in Butterflies and Moths (Insecta, Lepidoptera) - Marco, Heather G.; Šimek, Petr; Gäde, Gerd (Frontiers in Physiology, 2020)
Lepidoptera is amongst one of the four most speciose insect orders and ecologically very successful because of their ability to fly. Insect flight is always aerobic and exacts a high metabolic demand on the animal. A family of structurally related neuropeptides, generically referred to as adipokinetic hormones (AKHs), play a key role in triggering the release of readily utilizable fuel metabolites into the hemolymph from the storage forms in the fat body. We used mass spectrometry to elucidate AKH sequences from 34 species of Lepidoptera and searched the literature and publicly available databases to compile (in a phylogenetic context) a comprehensive list of all Lepidoptera sequences published/predicted from a total of 76 species. We then used the resulting set of 15 biochemically characterized AKHs in a physiological assay that measures lipid or carbohydrate mobilization in three different lepidopteran species to learn about the functional cross-activity (receptor-ligand interactions) amongst the different butterfly/moth families. Our results include novel peptide structures, demonstrate structural diversity, phylogenetic trends in peptide distribution and order-specificity of Lepidoptera AKHs. There is almost an equal occurrence of octa-, nona-, and decapeptides, with an unparalleled emphasis on nonapeptides than in any insect order. Primitive species make Peram-CAH-II, an octapeptide found also in other orders; the lepidopteran signature peptide is Manse-AKH. Not all of the 15 tested AKHs are active in Pieris brassicae; this provides insight into structure-activity specificity and could be useful for further investigations into possible biorational insecticide development.